Application audit technology based on the combination of cloud and terminal - Yongjun HUANG; Dongxin LIU; Huamin JIN; Guorong LIU; Laifu WANG; Jun SHEN (Dianxin kexue)
The flourish and popularity of Android terminals have greatly changed the peoples’ daily life and also brought new conditions to the internet Dark Industry Chain.The features of advanced malicious programs on intelligent terminals,and the reasons why an audit method of network activities was needed were discussed.At last,a solution was proposed,including the data collecting,the process of auditing and the management of audit policies.